2009
DOI: 10.1158/1078-0432.ccr-08-2080
|View full text |Cite
|
Sign up to set email alerts
|

Human Equilibrative Nucleoside Transporter 1 and Human Concentrative Nucleoside Transporter 3 Predict Survival after Adjuvant Gemcitabine Therapy in Resected Pancreatic Adenocarcinoma

Abstract: Purpose: Gemcitabine is a promising adjuvant treatment for patients with resected pancreatic adenocarcinoma and its use in combination with radiotherapy is under exploration. Human equilibrative nucleoside transporter 1(hENT1) and human concentrative nucleoside transporter (hCNT) 1and 3 are the major transporters responsible for 2 ¶,2 ¶-difluoro-2-deoxycytidine (gemcitabine) uptake into cells. The aim of this study was to determine patients' outcome according to the expression of hENT1 and hCNT3 in tumoral cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 37 publications
3
160
1
4
Order By: Relevance
“…Gemcitabine is taken up into cells primarily by human concentrative nucleoside transporter 1 and 3 (hCNT1 and hCNT3) and by human equilibrative nucleoside transporter (hENT1) [18]. The expression of these nucleoside transporters is correlated with chemosensitivity and patient survival [19][20][21][22][23]. After being taken into the cells, gemcitabine is activated by deoxycytidine (dCK) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is taken up into cells primarily by human concentrative nucleoside transporter 1 and 3 (hCNT1 and hCNT3) and by human equilibrative nucleoside transporter (hENT1) [18]. The expression of these nucleoside transporters is correlated with chemosensitivity and patient survival [19][20][21][22][23]. After being taken into the cells, gemcitabine is activated by deoxycytidine (dCK) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…5,30 Many studies have shown that the hENT1 but also hCNT3 expression determination can be used as a prognostic marker to provide prospective evaluations for patients receiving gemcitabine-based adjuvant therapy. 6,31,32 In L1210 murine leukaemia cells made resistant to ara-C and cross-resistant to gemcitabine, altered action of dCK can be observed, due to genomic recombination. 27 These results suggest that a partial deletion of the dCK gene observed after selection in the presence of gemcitabine is involved with resistance to this agent both in vitro and in vivo.…”
Section: Resistancementioning
confidence: 99%
“…Human equilibrative nucleoside transporter-1 (hENT1) and human concentrative nucleoside transporter-3 (hCNT3) both have important roles in the cellular uptake of the nucleoside analog gemcitabine (8). Consistent with this role, PDAC patients with low expression of hENT1 and hCNT3 have significantly worse survival after gemcitabine treatment compared with patients with high hENT1 and hCNT3 expression (9)(10)(11)(12). Although hENT1 expression is currently being evaluated as a biomarker to predict patient response to gemcitabine (13), the molecular mechanisms regulating hENT1 and hCNT3 expression in the PDAC tumor microenvironment are largely unknown.…”
Section: Introductionmentioning
confidence: 96%